Theory and methods in political science - Lowndes, Vivien; Marsh, David 1946-; Stoker, Gerry (Basingstoke, Hampshire Palgrave Macmillan, 2018)
Now with substantial extra coverage of methodological issues and an additional chapter on the philosophy of politics, this widely-used text introduces students to the approaches and methods of political science.
Includes bibliographical references and index.
Keywords: Political science; Political science -- Methodology